HELLO PARENTS APPLICATIONS: DEVELOPMENT OF WEB-BASED SCHOOL ADMINISTRATION SYSTEM - Ninda Dwi Astuti; Chandra Gupta; Febri Setiani (AL-ISHLAH: Jurnal Pendidikan, 2020)
The development of technology is currently developing very rapidly. This needs to be utilized in education, especially school agencies. Because currently there are many school activities that need to be developed so that the school system can develop for the better. The purpose of this study is to (1) facilitate the school administration system (2) make it easier for parents to see student’s academic development (3) create innovation in the school administration system. The method used in this study uses a qualitative approach and is developed with the waterfall model. The results of this study are the application design "Hello Parents" which is an application development system administration in web-based schools. This application contains big data in the form of school information, teacher information, student report cards, payments, school agenda, and student academic development.